TROPICAL ARCHITECTURE: THE ANALYSIS OF THREE WORKS BY ARCHITECT BRUNO STAGNO - Sant’Anna, Silvio Stefanini; Meirelles, Célia Regina Moretti; Moraes, Vivian Cardoso; Marcondes, Flavio; Fehr, Lucas; Raia, Fabio; de Oliveira Junior, Jair Antonio; Michelin, Guilherme Antonio (Seven Editora, 2025)
This work analyzes three buildings by architect Bruno Stagno: the BATCCA with the headquarters of the offices of the Bat tobacco company in Central America, built in 2006, the Casa LOUMAY in 2012 and the hotel to receive students from the Instituto Centroamericano de Administración de Empresas INCAE in 2016. The objective of this article is to understand the work of the Costa Rican in the context of sustainable tropical architecture applied to different typologies: business, residential and student hospitality. The methodological procedures are based on literature review and qualitative analysis, comparing bioclimatic strategies in the use of materials, the project, the elements of the envelope and the landscape, without leaving aside the emblematic meaning of the works. The results demonstrate conceptual consistency through the adaptation of sustainability premises in different contexts. BATCCA’s work has a business nature; Casa LOUMAY contemplates everyday family life; and at INCAE. Hospitality to receive students. In the three works analyzed, it is observed that he intertwines technical solutions with environmental ones, incorporating the cultural context of tropical architecture. This expands the debate on sustainable architecture, seeking user comfort and lower energy expenditure. DOI: https://doi.org/10.56238/sevened2025.029-115